The interactive effects of climate and land-use changes on soil water erosion across China under shared socioeconomic pathways - Yujin Xia; Wen Dai; Qigen Lin; Yuqi Wang; Wei Shao; Guojie Wang (Journal of Hydrology, 2026)

Correction: Identifying human activities and rainfall impacts in landslide: a case study from southwestern China - Xia Wang; Ying Wang; Qigen Lin; Xudong Yang (Natural Hazards, 2026)

Cold exposure triggers distinct RNA editing, alternative splicing, and gene expression patterns in cold domestication pufferfish (Takifugu obscurus) - Shuang Han; Jie Wang; Yuhao Luo; Jingping Zhang; Youquan Wang; Taixing Lin; Boyan Xu; Qigen Liu; Liangbiao Chen (Fish & Shellfish Immunology, 2026)

Identifying human activities and rainfall impacts in landslide: a case study from southwestern China - Xia Wang; Ying Wang; Qigen Lin; Xudong Yang (Natural Hazards, 2025)

Adaptive Evolution for Freshwater Adaptation in Coilia nasus by Directional Selection on Osmoregulation Genes - Shuang Han; Jie Wang; Taixing Lin; Jingping Zhang; Adelino V. M. Canario; Qigen Liu; Liangbiao Chen (Molecular Ecology, 2025)
The molecular mechanisms underlying the adaptation to freshwater habitats in fish of marine origin remain unclear. Grenadier anchovies, such as Coilia nasus , originate from marine environments and include both anadromous and freshwater‐resident conspecifics, making them ideal for studying adaptive evolution from marine to freshwater habitats. We conducted a comparative population genomic and transcriptome analysis of two distinct C. nasus lineages, one anadromous and the other freshwater‐resident, collected from mainstream and estuarine regions of the Yangtze River, China. By genome‐wide genotyping of the anadromous and the freshwater‐resident populations, we observed significant divergence in osmoregulation, energy metabolism, and immune response pathways associated with ecological adaptation and energy expenditure for migration. Some ion transport genes such as CAMK1 , ATP1α3 , KCNJ1 and SLC30A2 were identified that may contribute to freshwater adaptation. Notably, numerous mineralocorticoid signalling genes (e.g., NR3C2 , SGK1 , ATP1α3 , KCNJ1 ) exhibit dynamic change between the anadromous and freshwater populations, suggesting an important role for the hormone cortisol in regulating salinity acclimation in euryhaline fish. Among these genes, the ion channel ATP1α3 experienced adaptive amino acid substitutions (Val317Ile and Thr329Ser), which appear to be evolutionary hotspots across migratory species based on ortholog comparisons. These variants may facilitate sodium/potassium transport and highlight salinity tolerance as a key driver of divergence in anadromous fish transitioning to freshwater. These results enhance our understanding of the genetic basis underlying freshwater adaptation for an anadromous fish across osmotic boundaries.

Towards More Efficient Urban Flood Assessment: Issue of Spatial Resolution in Urban Flood Hydrodynamic Modeling from Flood Exposure Perspective - Yun Xing; Dong Shao; Qigen Lin; Irfan Ullah; Junsheng Wang; Yuezhu Wang (Water Resources Management, 2025)

A modeling framework for assessing the future changes in the occurrence of extreme rain-induced landslides - Xinlong Zhang; Qigen Lin; Manhoi Lok; Taosheng Huang; Xuan Yu; Weiping Wang; Ping Shen (Gondwana Research, 2025)

Di-(2-ethylhexyl) phthalate exposure induces premature testicular senescence by disrupting mitochondrial respiratory chain through STAT5B-mitoSTAT3 in Leydig cell - Haiming Cao; Qigen Xie; Peng Luo; Jiaqi Chen; Kai Xia; Lin Ma; Demeng Chen; Chunhua Deng; Zi Wan (GeroScience, 2024)

Overlooked fluorine deficiency in children of South and East China may be exacerbated by climate change: Evidence from the national assessment - Lingfeng Zhou; Weigang Liang; Yaobin Meng; Xiaoli Zhao; Fei Guo; Lingling Liu; Wenjing Li; Miaomiao Teng; Fanhao Song; Zhiqiang Cao; Yidong Mi; Qigen Lin; et al. (Journal of Cleaner Production, 2024)

Influence of Rice Straw Biochar Application on Soil Nutrient Dynamics and Rice Productivity Under Different Irrigation Regimes - Le Chen; Lin Guo; Xueyun Deng; Xiaohua Pan; Xiaobing Xie; Xueming Tan; Ping Liao; Qiangqiang Xiong; Qigen Dai; Hui Gao; Haiyan Wei; Yongjun Zeng; et al. (Journal of Soil Science and Plant Nutrition, 2023)

Projected land use changes in the Qinghai-Tibet Plateau at the carbon peak and carbon neutrality targets - Runhong Xu; Peijun Shi; Miaoni Gao; Yanjun Wang; Guojie Wang; Buda Su; Jinlong Huang; Qigen Lin; Tong Jiang (Science China Earth Sciences, 2023)

Rice straw biochar reduces Cd accumulation and promotes Cu accumulation in rice: irrigation regime is the driving factor - Le Chen; Lin Guo; Ping Liao; Qiangqiang Xiong; Xueyun Deng; Hui Gao; Haiyan Wei; Qigen Dai; Xiaohua Pan; Yongjun Zeng; Hongcheng Zhang (Journal of Soils and Sediments, 2023)

The influences of the spatial extent selection for non-landslide samples on statistical-based landslide susceptibility modelling: a case study of Anhui Province in China - Chuhan Wang; Qigen Lin; Leibin Wang; Tong Jiang; Buda Su; Yanjun Wang; Sanjit Kumar Mondal; Jinlong Huang; Ying Wang (Natural Hazards, 2022)

Assessing the spatiotemporal impact of climate change on event rainfall characteristics influencing landslide occurrences based on multiple GCM projections in China - Qigen Lin; Ying Wang; Thomas Glade; Jiahui Zhang; Yue Zhang (Climatic Change, 2020)

Spatial and temporal analysis of a fatal landslide inventory in China from 1950 to 2016 - Qigen Lin; Ying Wang (Landslides, 2018)

Spatial pattern and influencing factors of landslide casualty events - Ying Wang; Qigen Lin; Peijun Shi (Journal of Geographical Sciences, 2018)

Molecular evaluation on the distribution, diversity, and toxicity of Microcystis (Cyanobacteria) species from Lake Ulungur—a mesotrophic brackish desert lake in Xinjiang, China - Shen Lin; Jianzhong Shen; Yang Liu; Xingqiang Wu; Qigen Liu; Renhui Li (Environmental Monitoring and Assessment, 2011)